Efficiency enhancement by simulation method of Copper Antimony Disulfide thin film based solar cells. (June 2022) - Moujoud, Salaheddine; Hartiti, Bouchaib; Touhtouh, Samira; Fadili, Salah; Faddouli, Ali; Belhora, Fouad; Stitou, Mohamed; Hajjaji, Abdelowahed
Abstract: In this work we investigated by SCAPS-1D several effects on the performance of CuSbS2 based solar cell. The simulated baseline structure is Al/ZnO:Al/i-ZnO/CdS/CuSbS2 /Mo which is inherited from the structure of CIGS based solar cells. We studied the effect of buffer layer thickness which gave us as an optimum value 0.1 µm. As for CdS carrier density 10 18 cm −3 is the optimum value. After that, temperature effect has been checked too it is demonstrated that increasing temperature lead to lower the cell performance. In addition, the effect of work function showed that Molybdenum is a good element for back contact. Then, conduction band offset has been investigated. It is demonstrated that this value is critical. The efficiency increased from 4.8% to 15.74% for − 0.8 eV and − 0.2 eV CBO values. Finally and in order to reduce the toxicity of the device we decided to design cadmium free solar cells. SnS2 and In2 S3 are chosen as buffer layer candidate. They showed good performance especially SnS2 with an efficiency of 16.21%. Graphical Abstract: ga1